2009
DOI: 10.1007/s00167-009-0887-9
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical comparison of shape memory compression staples and mechanical compression staples: compression or distraction?

Abstract: Compression staples are a popular form of fixation for osteotomy and arthrodesis. "Mechanical compression" or "shape memory" designs are commercially available. We performed a biomechanical study comparing these designs. A load cell measured compression across a simulated fusion site. The two designs available were tested and compared. The effect of altering staple limb length was also assessed. The limbs of all mechanical compression staples diverged causing inconsistent compression and distraction. Shape mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…While a number of other studies have evaluated the biomechanical properties of different fixation methods for the Lapidus arthrodesis ( 3 , 5 , 9 , 17 , 18 , 21 28 ), variations in models and testing methods make meaningful comparison difficult. When comparing the rigidity of crossed-screw constructs with locking plates in a cadaveric study, Gruber et al ( 21 ) reported peak loads in four-point bending of 110.8 and 120.4 N, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While a number of other studies have evaluated the biomechanical properties of different fixation methods for the Lapidus arthrodesis ( 3 , 5 , 9 , 17 , 18 , 21 28 ), variations in models and testing methods make meaningful comparison difficult. When comparing the rigidity of crossed-screw constructs with locking plates in a cadaveric study, Gruber et al ( 21 ) reported peak loads in four-point bending of 110.8 and 120.4 N, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated the compressive properties and recovery behavior of SMA staples in different models. Using a small load cell fitted between two perspex blocks, Farr et al ( 17 ) reported a peak contact force of 35 N generated by a 20 × 20 Memotech SMA staple. A similar result was recorded by Shibuya et al ( 11 ) using a pressure sensor in a sawbones calcaneus model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once placed into bone, the warmer body temperature causes the staple tines to compress to a more rigid, closed position and maintain uniform compression. 17 Given the potential advantages of staple fixation treatment in SLIL injuries and the successful application of Nitinol staple fixation for other orthopedic procedures, we aimed to investigate the use of Nitinol staple fixation in the treatment of acute SLIL injuries using a cadaver model. The purpose of this study was to compare scaphoid and lunate motion in normal wrists to motion after SLIL fixation using the traditional K-wire fixation technique and 2-tine Nitinol staple fixation.…”
mentioning
confidence: 99%
“…Once placed into bone, the warmer body temperature causes the staple tines to compress to a more rigid, closed position and maintain uniform compression. 17 …”
mentioning
confidence: 99%